Southeast Asia's subversive voters a Philippine perspective - Thompson, Mark R. (Philippine studies : historical and ethnographic viewpoints, 2016)
"In the Philippines and other Southeast Asian countries poor people's voting behavior has been subversive of elite interests, causing the upper classes to be skeptical of votes cast by the poor and to "educate" them on the "proper" exercise of suffrage. But voting by the poor can be understood within a "moral economy" framework in which communal interests transcend utilitarian calculations. Populist politicians (Joseph Estrada in the Philippines and Thaksin Shinawatra in Thailand) have brought localist voting patterns to the national level, resulting in adverse reactions: an elite-led insurrection ousted Estrada in 2001, while the Thai military staged the coup of 2014 to break the electoral bond between pro-Thaksin politicians and the poor."